Evaluation of pre-workout and recovery formulations on body composition and performance after a 6-week high-intensity training program - Cabre, Hannah E.; Gordon, Amanda N.; Patterson, Noah D.; Smith-Ryan, Abbie E. (Frontiers in Nutrition, 2022)
Activities such as high-intensity resistance training (HIRT) and high-intensity interval training (HIIT) may be more time-efficient modes to stimulate rapid changes in performance and body composition. There is little research evaluating the combined effects of HIRT and HIIT on body composition and strength, particularly when paired with nutritional supplementation. PURPOSE: To evaluate the chronic effects of pre- and post-workout supplementation on body composition and strength, and to understand sex-specific responses. METHODS: 64 untrained males (n=23) and females (n=41) (mean±standard deviation; Age: 33.2±10.0 yrs; %fat: 31.6±7.4%) were randomized to either 1) pre-post supplementation [SUP (n=25); pre=multi-ingredient caffeine/HMB/vit D; post=whey protein/carbohydrates/glucosamine/vitamins], 2) placebo [PL (n=24); non-caloric], or 3) control [CON (n=15)]. All participants completed one repetition max (1RM) strength testing for leg press and bench press at baseline and week 6. Estimates of fat mass (FM) and lean mass (LM) were measured via dual energy x-ray absorptiometry. Participants in the SUP or PL group completed a 6-week supervised exercise intervention consisting of a full-body HIRT workout (3×6-8 reps) followed by a HIIT treadmill run (6×1min run:1min rest) twice per week. Outcomes were evaluated by separate repeated measure ANOVAs (2×3). RESULTS: There were no differences in FM between groups or sex (p=0.133-0.851). LM increased from baseline to post-testing for all groups [Mean difference [MD(Post-Pre)±Standard Error (SE)= 0.78±0.12 kg; p<0.001]. While not significant (p=0.081), SUP gained more LM compared to PL [MD(SUP-PL)±SE=3.5±3.3 kg] and CON [MD(SUP-CON)±SE=5.2±3.8 kg]. LM increased over time for both males (0.84±0.24 kg; p=0.003) and females (0.73±0.14 kg; p<0.001). The SUP group resulted in a significant increase in 1RM leg press compared to the CON group (89.9±30.8 kg; p=0.015), with no significant differences compared to PL (p=0.409). The SUP group had greater increases in 1RM bench press compared to the CON group (9.8±1.8 kg; p<0.001), with no significant differences compared to PL (p=0.99). Both sexes increased upper- (5.5±0.7 kg; p<0.001) and lower-body strength (69.8±4.5 kg p<0.001) with training. CONCLUSIONS: Nutrient supplementation timing appears to augment body composition changes and strength compared to control. Pre-/post-nutrient timing may support greater increases in LM and lower- and upper-body strength in both men and women.